Intelligent systems for computer modelling : proceedings of the 1st European-Middle Asian Conference on Computer Modelling 2015, EMACOM 2015 /: proceedings of the 1st European-Middle Asian Conference on Computer Modelling 2015, EMACOM 2015. ([2016]) - Unknown
No abstract available